The thermodynamics of inclusion complex of phenobarbital with hydroxypropyl-Î²-cyclodextrin - Martodihardjo, Suwaldi; Isadiartuti, Dewi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Cyclodextrins are cyclic oligosaccharides which have been used extensively to improve the solubility in the formation of inclusion complex. The ability of cyclodextrin to form an inclusion complex has been attributed to factors including size of cyclodextrin cavity to the guest molecule and thermodynamics of their interactions.In this study, complex formation of phenobarbital and hidroxypropyl-Î²-cyclodextrin in the acetate buffer 0.01 M pH 4.4 and phosphate buffer 0.01 M pH 7.4 all with Î¼ =0.10 and at temperatures of 32.o, 37.o, and 42oÂ±0.5oC were determined.The results showed that phenobarbital formed inclusion complex with hidroxypropyl-Î²-cyclodextrin. The interaction shown a negative enthalphy (Î”H < 0 ), a spontaneous processes (Î”G < 0) and an increase in the entropy of the system (Î”S > 0).Key words : phenobarbital and hidroxypropyl-Î²-cyclodextrin, inclusion complex, thermodynamics